The link between copper and Wilson's disease. (1st September 2013) - Purchase, Rupert
Wilson's disease (hepatolenticular degeneration) is a rare inherited autosomal recessive disorder of copper metabolism leading to copper accumulation in the liver and extrahepatic organs such as the brain and cornea. Patients may present with combinations of hepatic, neurological and psychiatric symptoms. Copper is the therapeutic target for the treatment of Wilson's disease. But how did copper come to be linked with Wilson's disease? The answer encompasses a study of enzootic neonatal ataxia in lambs in the 1930s, the copper-chelating properties of British Anti-Lewisite, and the chemical analysis for copper of the organs of deceased Wilson's disease patients in the mid-to-late 1940s. Wilson's disease is one of a number of copper-related disorders where loss of copper homeostasis as a result of genetic, nutritional or environmental factors affects human health.